PEMBUATAN KARBON AKTIF DARI LIMBAH CANGKANG KELAPA SAWIT (Elaeis guineensis) MENGGUNAKAN ULTRASONIK - Tirta Suci Dhian Kasih; M Taufik; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2020)
Activated carbon from palm kernel shell has been prepared by using ultrasonic assisted activation.  Carbonization was conducted at mild condition of 400ºC for 90 minutes heating time.  Ultrasonic irradiation (35 Watt,  42 KHz) for 15 minutes increases the carbon iodine number from 452.4021 mg/g  up to 817.4907 which is higher than SNI 06-3730-1995 requirement of mg/ g 750 mg/g for activated carbon. FTIR spectra results show that activated carbon has -OH groups at wave numbers of 3000-3500 cm-1, C = C at wave numbers of 1550-1650 cm-1, CO at wave numbers of 1000-1260 cm-1 and CH at wave numbers of 810- 770 cm-1 . Adsorption test results showed that the prepared activated carbon was able to absorb Pb+2 ion at the optimum concentration of 60 mg/L. Adsorption isotherm study conducted by Freundlich equation produces a regression coefficient R2 = 0.835 with a maximum absorption capacity of 11.0783mg/ g.